Risks and Care Framework for Pregnancy with Chronic Kidney Disease - Djurabekova S. T (European Journal of Life Safety and Stability (2660-9630), 2024)
Chronic kidney disease (CKD) affects 9.1% of the global population, with increasing cases among women of reproductive age. Managing pregnancy in CKD patients is challenging, especially due to limited understanding of risks across different CKD stages, particularly regarding disease progression, dialysis, and post-transplant care. Women in advanced CKD stages (3-5) face significant risks, including a 46% chance of kidney function decline within a year postpartum. Pre-eclampsia affects up to 40% of pregnancies, increasing complications like preterm birth and low birth weight. Women on dialysis or post-transplant care require frequent monitoring and medication adjustments. The study emphasizes the need for early, personalized care and a multidisciplinary approach to improve outcomes for both mother and child. Better screening and tailored management strategies are crucial to addressing these risks and optimizing care for high-risk pregnancies. Keywords: Chronic kidney disease (CKD), Pregnancy, Maternal health, Fetal health, Pregnancy complications, Risk factors, Management, Multidisciplinary care, Outcomes.